The Effectiveness of Cooperative Learning Model of Pair Checks Type on Motivation and Mathematics Learning Outcomes of 8th Grade Junior High School Students - Wicaksono, Wahyu Budi; Mashuri, Mashuri; Veronica, Rahayu Budhiati (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this research was to know the effectiveness of Pair Checks cooperative model towards students’ learning result and learning motivation of eight grade. Population of this research were students of eight grade Junior High School 2 Pati in the academic year 2016/1017. The research used cluster random sampling technique.Where the selected samples were students of class VIII H as experimental class and class VIII G as control class. The data collected by the method of documentation, test methods, and scale methods. The analyzed of data used completeness test and average different test. The results showed that: (1) students’ learning result who join Pair Checks cooperative model have classical study completeness; (2) students’ mathematics learning result who join Pair Checks cooperative model is better than students mathematics learning result who join ekspository learning; (3) students’ learning motivation who join Pair Checks cooperative model is better than students’ learning motivation who join ekspository learning.